Calibration and validation of the DNDC model to estimate nitrous oxide emissions and crop productivity for a summer maize-winter wheat double cropping system in Hebei, China. (July 2020) - Abdalla, M.; Song, X.; Ju, X.; Topp, C.F.E.; Smith, P.
Abstract: The main aim of this paper was to calibrate and evaluate the DeNitrification-DeComposition (DNDC) model for estimating N2 O emissions and crop productivity for a summer maize-winter wheat double cropping system with different N fertilizer rates in Hebei, China. The model's performance was assessed before and after calibration and model sensitivity was investigated. The calibrated and validated DNDC performed effectively in estimating cumulative N2 O emissions (coefficient of determination (1:1 relationship; r 2 ) = 0.91; relative deviation (RD) = −13 to 16%) and grain yields for both crops (r 2  = 0.91; RD = −21 to 7%) from all fertilized treatments, but poorly estimated daily N2 O patterns. Observed and simulated results showed that optimal N fertilizer treatment decreased cumulative N2 O flux, compared to conventional N fertilizer, without a significant impact on grain yields of the summer maize-winter wheat double cropping system. The high sensitivity of the DNDC model to rainfall, soil organic carbon and temperature resulted in significant overestimation of N2 O peaks during the warm wet season. The model also satisfactorily estimated daily patterns/average soil temperature ( o C; 0–5 cm depth) (r 2  = 0.88 to 0.89; root mean square error (RMSE) = 4 °C; normalized RMSE (nRMSE) = 25% and index of agreement (d) = 0.89–0.97) but under-predicted water filled pore space (WFPS; %; 0–20 cm depth) (r 2  = 0.3 to 0.4) and soil ammonium and nitrate (exchangeable NH4 + & NO3 − ; kg N ha −1 ; r 2  = 0.97). With reference to the control treatment (no N fertilizer), DNDC was weak in simulating both N2 O emissions and crop productivity. To be further improved for use under pedo-climatic conditions of the summer maize-winter wheat double cropping system we suggest future studies to identify and resolve the existing problems with the DNDC, especially with the control treatment. Graphical abstract: Crop sequence of the maize and wheat crops in the summer maize-winter wheat double cropping system. Image 1 Highlights: Calibrated DNDC effectively estimated cumulative N2 O flux and grain yields. High sensitivity of DNDC to input parameters resulted in overestimation of N2 O peaks. DNDC was weak in simulating control treatment. DNDC satisfactorily estimated soil temperature but under-predicted WFPS and soil N. Optimal N fertilizer decreased N2 O flux without a significant impact on grain yields. Abstract : The calibrated DNDC model effectively estimated cumulative N2 O emissions, grain yields and soil temperature but underestimated WFPS and soil N, in a winter wheat-summer maize double cropping system.